Recent Advances in the Fabrication of Membranes Containing “Ion Pairs” for Nanofiltration Processes - Ji, Yan-Li (Polymers (Basel), 2017)
In the face of serious environmental pollution and water scarcity problems, the membrane separation technique, especially high efficiency, low energy consumption, and environmental friendly nanofiltration, has been quickly developed. Separation membranes with high permeability, good selectivity, and strong antifouling properties are critical for water treatment and green chemical processing. In recent years, researchers have paid more and more attention to the development of high performance nanofiltration membranes containing “ion pairs”. In this review, the effects of “ion pairs” characteristics, such as the super-hydrophilicity, controllable charge character, and antifouling property, on nanofiltration performances are discussed. A systematic survey was carried out on the various approaches and multiple regulation factors in the fabrication of polyelectrolyte complex membranes, zwitterionic membranes, and charged mosaic membranes, respectively. The mass transport behavior and antifouling mechanism of the membranes with “ion pairs” are also discussed. Finally, we present a brief perspective on the future development of advanced nanofiltration membranes with “ion pairs”.